PARTISIPASI MASYARAKAT BULUKUMBA DALAM PEMBANGUNAN DAERAH DI KALIMANTAN TIMUR - Muhammad Sultan; Sunardi Sunardi; Ilham Abu (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2021)
The progress of the development of a region is not only the responsibility of the government, but requires active participation from all components of society. Good collaboration between local government and communities is an important factor in achieving this. This research is a descriptive qualitative type to describe the participation of the Bulukumba community in regional development in East Kalimantan. The research sample is the head of the family or resident's representative in a house that is domiciled in East Kalimantan, as many as 60 people who were selected by accidental sampling. Collecting data using online questionnaires in the form of Google form and distributed to respondents via Whatsapp Group social media and analyzed descriptively and presented in the form of frequency tables and graphs with narration. In addition, to deepen the required information, 3 informants were selected. The technique of collecting information through indepth interviews uses interview guides to informants and is then analyzed qualitatively. The results showed that most of the people of Bulukumba had participated well in regional development in East Kalimantan. Even so, it was still found that the Bulukumba community did not participate in development due to various factors, including a lack of public understanding of the importance of participatory development. Therefore, it is necessary to have active outreach activities from the local government and all components of society regarding the importance of community participation for the realization of advanced and sustainable regional development.